Analisis Potensi Likuefaksi Berdasarkan Metode Global Geospatial Model di Kecamatan Sanden Kabupaten Bantul Yogyakarta - Annas, Mohamad Chairul; Niyartama, Thaqibul Fikri; Wibowo, Nugroho Budi (Sunan Kalijaga Journal of Physics, 2021)
This research is motivated by the liquefaction phenomenon that has occurred in Yogyakarta area due to the 2006 earthquake. This study aims to find out the probability of liquefaction based on the Global Geospatial Model (GGM) method and create a map of the distribution of liquefaction-prone settlements. This research was conducted in Sanden Subdistrict in the southern part of Bantul Regency. The GGM method utilizes three main parameters: shear wave speed at a depth of 30 meters (Vs30), acceleration of ground vibration (PGA) and ground wetness index (CTI). Vs30 is derived from the inverse method of microtremor measurement results, PGA is obtained from the PUSKIM website and the CTI value is obtained from the Centre for Ecology and Hydrology's (CEH) website. The results showed that vs30 values ranged from 154.66 m / s to 260.80 m / s, CTI values ranged from 5.45 to 9.28 and PGA values ranged from 0.52 g to 0.67 g. The potential for liquefaction occurred throughout Sanden Subdistrict with a probability value of > 0.99 and the highest distribution of likuefkasi-prone settlements in the east of the research area.